Effect of Holding Time and Temperature of Hot Pressing on Tensile Strength of Biodegradable Plastic Made of Carrageenan - Fitrian Imaduddin; Palgunadi Sastra; Wijang Wisnu Raharjo; Putri Wullandari; Ridwan Ridwan (Universitas Sebelas Maret, 2022)
Biodegradable plastic can be made from carrageenan by the hot press method. This method can make biodegradable plastic with large dimensions. However, the plastic quality depended on the holding time, temperature, and pressure selected during the hotpressing process. Therefore, this research is conducted to determine the effect of holding time and temperature in the hot press process on the tensile strength of biodegradable plastic made from carrageenan. The composition of the biodegradable plastic material used was 35% carrageenan, 35% polyvinyl alcohol, and 30% glycerol. The tensile strength of the composite was observed through tensile testing using a universal testing machine. fourier-transform infrared spectroscopy, X-ray Diffraction (XRD), and Scanning Electron Microscopy (SEM) tests were also conducted to sharpen the analysis. The addition of holding time led to an increase in the tensile strength of biodegradable plastics. The highest tensile strength was obtained at a holding time of 30 minutes with a value of 4.45 MPa. After 30 minutes, the tensile strength of the biodegradable composite decreased. Meanwhile, the addition of process temperature caused a decrease in the tensile strength of biodegradable plastics. The highest tensile strength was obtained at a process temperature of 100 °C with a value of 5.28 MPa.